2001
DOI: 10.1016/s0002-9440(10)61684-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary Renal Neoplasms with the ASPL-TFE3 Gene Fusion of Alveolar Soft Part Sarcoma

Abstract: The unbalanced translocation, der(17)t(X;17)(p11.2;q25), is characteristic of alveolar soft part sarcoma (ASPS). We have recently shown that this translocation fuses the TFE3 transcription factor gene at Xp11.2 to ASPL, a novel gene at 17q25. We describe herein eight morphologically distinctive renal tumors occurring in young people that bear the identical ASPL-TFE3 fusion transcript as ASPS, with the distinction that the t(X;17) translocation is cytogenetically balanced in these renal tumors. A relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
148
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 559 publications
(150 citation statements)
references
References 31 publications
1
148
1
Order By: Relevance
“…Clinicopathologic features of other renal neoplasms with recurrent translocations involving TFE3 have been described (19,34). These tumors include the ''ASPL-TFE3 renal carcinomas'' showing t(X;17)(p11.2;q25) (19), and ''PRCC-TFE3 renal carcinoma'' showing t(X;1)(p11.2;q21) (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicopathologic features of other renal neoplasms with recurrent translocations involving TFE3 have been described (19,34). These tumors include the ''ASPL-TFE3 renal carcinomas'' showing t(X;17)(p11.2;q25) (19), and ''PRCC-TFE3 renal carcinoma'' showing t(X;1)(p11.2;q21) (34).…”
Section: Discussionmentioning
confidence: 99%
“…These tumors include the ''ASPL-TFE3 renal carcinomas'' showing t(X;17)(p11.2;q25) (19), and ''PRCC-TFE3 renal carcinoma'' showing t(X;1)(p11.2;q21) (34). Like the t(6;11) tumors, these neoplasms seem primarily to affect children and young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have recently characterized an additional subset of RCCs characterized by a balanced t(X;17)(p11.2;q25), which results in a fusion of the ASPL (a.k.a. ASPSCR1 or PRCC2) and TFE3 genes (Argani et al, 2001b(Argani et al, , 2002Heimann et al, 2001). Notably, the ASPL-TFE3 gene fusion, arising from an unbalanced der(17) t(X;17)(p11;q25), was originally identified as the recurrent genetic aberration of alveolar soft part sarcoma (ASPS) .…”
mentioning
confidence: 99%
“…Notably, the ASPL-TFE3 gene fusion, arising from an unbalanced der(17) t(X;17)(p11;q25), was originally identified as the recurrent genetic aberration of alveolar soft part sarcoma (ASPS) . We have recently found that RCCs associated with PRCC-TFE3 or ASPL-TFE3 can be distinguished from each other by careful morphologic analysis, suggesting that differences in the TFE3 fusion partner can result in subtle but consistent phenotypic differences (Argani et al, 2001b(Argani et al, , 2002. Nonetheless, it is likely that some common features of all TFE3 fusion proteins underlie a common molecular pathogenesis of these cancers.…”
mentioning
confidence: 99%